2011
DOI: 10.1007/s12032-011-9866-3
|View full text |Cite
|
Sign up to set email alerts
|

Telomere shortening occurs early during gastrocarcinogenesis

Abstract: When telomeres are shortened to a critical length, they will initiate chromosomal instability (CIN) and may finally cause tumorigenesis. The purpose of the present study was to evaluate the shortened telomere as a potential biomarker for tumorigenesis in gastric carcinoma. The telomeres in matched cancer and adjacent noncancer mucosa samples from 86 gastric carcinoma patients were measured by real-time polymerase chain reaction (PCR). According to the International Union Against Cancer (UICC), tumor stages wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 21 publications
1
11
1
Order By: Relevance
“…These data are in contrast to the general model of the role played by telomeres in tumor development, i.e. telomere shortening as an early event in carcinogenesis (34,37). However, our results are consistent with several previous studies in which longer telomeres have been associated with absence of metastases in OSCC (35), a low grade in intracranial tumors (38), higher overall survival in lung cancer patients (36), and a lower risk of death in patients with prostate tumors (39).…”
Section: Discussioncontrasting
confidence: 92%
“…These data are in contrast to the general model of the role played by telomeres in tumor development, i.e. telomere shortening as an early event in carcinogenesis (34,37). However, our results are consistent with several previous studies in which longer telomeres have been associated with absence of metastases in OSCC (35), a low grade in intracranial tumors (38), higher overall survival in lung cancer patients (36), and a lower risk of death in patients with prostate tumors (39).…”
Section: Discussioncontrasting
confidence: 92%
“…In some types of cancers, such as gastric and bladder cancer, shorter RTL in leukocytes was a risk factor of tumorigenesis, [12,13,21] while it was opposite in lung and colorectal cancer. [17,18] …”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer not characterized by its DNA MMR status, increasing chromosomal instability, inactivation of p53 tumor suppression, and increasing tumor telomere shortening has been reported [106]. Another evaluation of gastric tumors reported that telomere length was shortest in early stage cancers and then lengthened with increasing stage [107]. In addition, telomere length was increased in the antral mucosa of patients successfully treated for H. pylori infection [108].…”
Section: The Gi Tract Cancers Telomeres and Telomere Maintenance Mementioning
confidence: 99%